Dense Plasma Focus: physics and applications (radiation material science, single-shot disclosure of hidden illegal objects, radiation biology and medicine, etc. (March 2015) - Gribkov, V A; Miklaszewski, R; Paduch, M; Zielinska, E; Chernyshova, M; Pisarczyk, T; Pimenov, V N; Demina, E V; Niemela, J; Crespo, M-L; Cicuttin, A; Tomaszewski, K; et al.
Abstract: The paper presents some outcomes obtained during the year of 2013 of the activity in the frame of the International Atomic Energy Agency Co-ordinated research project "Investigations of Materials under High Repetition and Intense Fusion-Relevant Pulses ". The main results are related to the effects created at the interaction of powerful pulses of different types of radiation (soft and hard X-rays, hot plasma and fast ion streams, neutrons, etc. generated in Dense Plasma Focus (DPF) facilities) with various materials including those that are counted as perspective ones for their use in future thermonuclear reactors. Besides we discuss phenomena observed at the irradiation of biological test objects. We examine possible applications of nanosecond powerful pulses of neutrons to the aims of nuclear medicine and for disclosure of hidden illegal objects. Special attention is devoted to discussions of a possibility to create extremely large and enormously diminutive DPF devices and probabilities of their use in energetics, medicine and modern electronics.